'Pony express' crowdsourcing logistics for last-mile delivery in B2C e-commerce: an economic analysis. Issue 5 (3rd September 2021) - Seghezzi, Arianna; Mangiaracina, Riccardo; Tumino, Angela; Perego, Alessandro
ABSTRACT: The last-mile delivery is one of the most challenging logistics issues arising from B2C e-commerce. Companies operating online have to meet stringent requirements in terms of service level; moreover, the features of e-commerce orders – e.g. small dimension – make last-mile delivery the most expensive part of the delivery process. In this context, crowdsourcing logistics emerges as an innovative and promising solution: deliveries are assigned to a network of 'common' people through an open call. This solution may imply great advantages for the urban society. Nonetheless, in order to spread, it has to be economically sustainable for companies. In this regard, the paper investigates the economic profitability of a 'pony express' crowdsourcing logistics initiative in an urban area. A model has been developed in order to estimate the cost of deliveries using crowdsourced services, and to compare it with the cost of 'traditional' pony express couriers.